Synthesis of novel polymerizable molecules bearing bisphosphonate. Issue 46 (7th October 2015) - Kachbi Khelfallah, S.; Monteil, M.; Deschamp, J.; Gager, O.; Migianu-Griffoni, E.; Lecouvey, M.
Abstract : In recent years, bisphosphonate chemistry has undergone an exponential growth due to the potential applications of these compounds in medicine and nanobiomaterial research. Abstract : In recent years, bisphosphonate chemistry has undergone an exponential growth due to the potential applications of these compounds in medicine and nanobiomaterial research. In this paper we describe the synthesis methods of different families of methacrylic monomers bearing a bisphosphonate with varying lengths of the chain, PEG linkers and more or less hydrolysable functions such as ester, carbamate or amide.